2007
DOI: 10.1590/s1413-86702007000600009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diarrhea: poor parental recall ability

Abstract: Several methodological issues may have an impact on the incidence rates of childhood acute diarrhea reported by community-based studies. This study was performed to assess the impact of parental recall ability and definition of diarrhea on the estimate of incidence of acute diarrhea. Eighty-four children younger than 40 months were randomly selected and visited every other day for four weeks and the occurrence of diarrhea was registered. On the last day of the study, another visit was performed and the informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…A fourth study limitation is that we used a 2-week recall on the presence of diarrhea and did not collection information on the number of episodes or the severity or duration of episodes. It has been established that recall periods beyond 2 days can underreport events 3336. Because of this tendency, we measured diarrheal disease prevalence conservatively, and therefore, the effect sizes given in this study are likely underestimates.…”
Section: Discussionmentioning
confidence: 96%
“…A fourth study limitation is that we used a 2-week recall on the presence of diarrhea and did not collection information on the number of episodes or the severity or duration of episodes. It has been established that recall periods beyond 2 days can underreport events 3336. Because of this tendency, we measured diarrheal disease prevalence conservatively, and therefore, the effect sizes given in this study are likely underestimates.…”
Section: Discussionmentioning
confidence: 96%
“…Although it is not clear which study provides the most accurate estimate, prospective cohort studies consistently report a lower frequency of acute gastroenteritis than cross-sectional surveys (Roy et al, 2006). The case definition used also has been shown to have an important impact on disease estimates (Majowicz et al, 2008 Evidence also exists that length of the recall period may impact estimates of the incidence of acute gastroenteritis, with a higher incidence of diarrhea being reported among both adults and children in developing countries when asked about shorter, more recent time periods (Ramakrishnan et al, 1999;Melo et al, 2007;Feikin et al, 2010). To examine the impact of recall period on estimates of the incidence of acute gastroenteritis in the United States, we designed the 2006-2007 The Foodborne Diseases Active Surveillance Network (FoodNet) Population Survey to address two specific questions: Would a 7-day recall period result in a higher prevalence of acute gastroenteritis than a 1-month recall period?…”
Section: Introductionmentioning
confidence: 99%
“…The line which ends highest represents the cumulative funds spent by the TSC, closely related to the reported coverage. Source: http://www.developmentbookshelf.com/doi/book/10.3362/9781780449449 -Saturday, May 12, 2018 11:58:23 AM -IP Address:34.214.212.150 recall data can be very unreliable (Alam et al, 1989;de Melo et al, 2007) 10 and coverage was assumed to be the same as usage, when it is widespread practice in rural India for some members of households with functioning toilets to defecate in the open some or all of the time .…”
Section: Untested Assumptions Without Ground-truthingmentioning
confidence: 99%
“…10. The Brazilian study (de Melo et al, 2007) found with visits every other day that over a four-week period, 33 out of 84 children under 40 months had diarrhoea but parental recall at the end of the period reported only 10. Issues included the understanding of what constituted diarrhoea.…”
Section: Notesmentioning
confidence: 99%